Influence of pre-harvest chitosan foliar spray on the performance and chemical attributes of washington navel orange trees in contrasting environments - Ahmed Hussien Hanafy Ahmed; Mohamed Ramadan Aboul-Ella Nesiem; Hesham Ali Allam (Global Journal of Plant and Soil Sciences, 2024)
The present study was carried out during 2012 and 2013 seasons to study the effect of pre-harvest foliar application of chitosan (a natural beta-1-4-linked glucosamine polymer) at two concentrations 250 and 500 ppm on vegetative tree growth, fruit yield and quality as well as leaves chemical composition of Washington navel orange trees grown under two locations. As for growth parameters (shoot length, leaves number, and leaves area), the results revealed that chitosan treatments had insignificant effect. Meanwhile, it had a significant improvement on most of the studied fruit characters and leaf chemical constituents, that is, pigments, sugars, total soluble phenols, total free amino acids, endogenous plant hormones “IAA, ABA and GA3” as well as leaf nutritional status “N, P, K, Zn, Ca, B and Si”. Generally, pre-harvest chitosan applications mostly had pronounced positive effects on improving navel orange quality, that is, fruit weight, firmness and T.S.S.%, especially at the rate 500 ppm.